ORAL COMMUNICATION APPREHENSION AND COMMUNICATIVE COMPETENCE WITH ELECTRICALENGINEERING UNDERGRADUATES IN UTeM - Indra Devi, S.; Feroz, Farah Shahnaz (Journal of Human Capital Development (JHCD), 2008)
This study attempted to determine if communication apprehension existed among electrical engineering students, their perceived communication competence, their general performance in the oral presentation skills and more specifically the possible correlations that existed between these elements. The instruments that were used for data collection in the study are the Self-Perceived Communication Competence Scale (SPCC), Personal Report of Communication Apprehension (PRCA-12) and a Presentation Evaluation Rubric. The findings revealed that the students fall under the modest group of speakers and they do have a moderate amount of communication anxiety but that does not affect their grades. The higher the students' perception of their communicative competence, there is less communication anxiety. The findings also indicate that there's no linear correlation between their levels of apprehension and lecturer evaluation but there does exist a linear relationship between their Self-Perceived Communication Competence and lecturer's evaluation meaning twhen they had more confidence on their competence, their tance in the presentation perform is better. Keywords: oral communication apprehension, communicative competence, oral presentation, electrical engineering undergraduates, confidence, performance